Dihydrofolate Reductase Deficiency Due to a Homozygous DHFR Mutation Causes Megaloblastic Anemia and Cerebral Folate Deficiency Leading to Severe Neurologic Disease - Cario, Holger; Smith, Desirée E.C.; Blom, Henk; Blau, Nenad; Bode, Harald; Holzmann, Karlheinz; Pannicke, Ulrich; Hopfner, Karl-Peter; Rump, Eva-Maria; Ayric, Zuleya; Kohne, Elisabeth; Debatin, Klaus-Michael; et al. (American journal of human genetics, 2011)
The importance of intracellular folate metabolism is illustrated by the severity of symptoms and complications caused by inborn disorders of folate metabolism or by folate deficiency. We examined three children of healthy, distantly related parents presenting with megaloblastic anemia and cerebral folate deficiency causing neurologic disease with atypical childhood absence epilepsy. Genome-wide homozygosity mapping revealed a candidate region on chromosome 5 including the dihydrofolate reductase ( DHFR) locus. DHFR sequencing revealed a homozygous DHFR mutation, c.458A>T (p.Asp153Val), in all siblings. The patients' folate profile in red blood cells (RBC), plasma, and cerebrospinal fluid (CSF), analyzed by liquid chromatography tandem mass spectrometry, was compatible with DHFR deficiency. DHFR activity and fluorescein-labeled methotrexate (FMTX) binding were severely reduced in EBV-immortalized lymphoblastoid cells of all patients. Heterozygous cells displayed intermediate DHFR activity and FMTX binding. RT-PCR of DHFR mRNA revealed no differences between wild-type and DHFR mutation-carrying cells, whereas protein expression was reduced in cells with the DHFR mutation. Treatment with folinic acid resulted in the resolution of hematological abnormalities, normalization of CSF folate levels, and improvement of neurological symptoms. In conclusion, the homozygous DHFR mutation p.Asp153Val causes DHFR deficiency and leads to a complex hematological and neurological disease that can be successfully treated with folinic acid. DHFR is necessary for maintaining sufficient CSF and RBC folate levels, even in the presence of adequate nutritional folate supply and normal plasma folate.